Respuesta :
We can transform this function by adding a constant to the original equation y=x^2. A new transformed function g(x) is given by g(x)=f(x)+c (where f(x)=y)
c>0 moves it up
c<0 moves it down
So: y=x^2+c
y=x^2-20
The new graph will be 20 units down the original.
Answer: The graph of the equation [tex]y=x^2[/tex] can be transformed to the graph of the equation [tex]y=x^2-20[/tex] by shifting [tex]y=x^2[/tex] 20 units downward.
Step-by-step explanation:
Some transformations for a function f(x):
If [tex]f(x)+k[/tex], the function is shifted "k" units upward.
If [tex]f(x)-k[/tex], the function is shifted "k" units downward.
Knowing these transformations and given these equations:
[tex]y=x^2[/tex] and [tex]y=x^2-20[/tex]
We can concluse that the graph of the equation [tex]y=x^2[/tex] can be transformed to the graph of the equation [tex]y=x^2-20[/tex] by shifting [tex]y=x^2[/tex] 20 units downward.